Harmonization of Accounting Standards for Islamic Financial Institutions: Evidence of the Adoption of FAS No. 17 in Indonesia - Andari, Dian (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
ABSTRACTIndonesia as a country with dual-banking system applies local accounting standards for conventional and Islamic financial institutions named SAK (Standar Akuntansi Keuangan or Generally Accepted Accounting Standard) which may raise the question of accounting harmonization with Financial Accounting Standards (FAS) issued by Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI). This study aims to analyze the harmony level of Islamic accounting in Indonesia to FAS issued by the AAOIFI. The analysis covers de jure (formal or regulatory) harmonization and de facto (practical) harmonization. It involves content analysis utilizing FAS no. 27 of investment accounts to Indonesian PSAK at de jure analysis, and to thirteen of Indonesian Islamic banks annual report in 2016 for de facto analysis. Wilcoxon signed rank test is conducted to measure the significance of harmony to AAOIFI standards. The result shows that there is no harmony in de jure and de facto level.ABSTRAKIndonesia sebagai negara dengan dual-banking system memiliki standar akuntansi keuangan (SAK) yang digunakan oleh lembaga keuangan konvensional dan syariah. Hal ini dapat menimbulkan pertanyaan tentang harmonisasi SAK dengan Financial Accounting Standards (FAS) yang dikeluarkan oleh Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI). Penelitian ini bertujuan untuk menganalisis tingkat keharmonisan akuntansi syariah di Indonesia terhadap FAS yang dikeluarkan oleh AAOIFI. Analisis ini mencakup harmonisasi de jure (formal atau secara regulasi) dan harmonisasi de facto (praktis). Penelitian ini melibatkan analisis konten menggunakan FAS no. 27 akun investasi ke PSAK Indonesia pada analisis de jure, dan tiga belas laporan tahunan bank syariah Indonesia pada tahun 2016 untuk analisis de facto. Tes peringkat uji Wilcoxon dilakukan untuk mengukur signifikansi keselarasan dengan standar AAOIFI. Hasilnya menunjukkan bahwa tidak ada harmonisasi antara FAS dan SAK dalam tingkat de jure dan de facto.